Indigenous entrepreneurship in timber furniture manufacturing: The Gumatj venture in Northern Australia - Pearson, Cecil; Helms, K. (International Foundation for Research and Development, 2011)
Despite commitment by the Australian Government to improve the economic independence of Indigenous people Aboriginals and Torres Strait Islanders they are the most socio economic disadvantaged group relative to other Australians. This commitment manifests in the four main strands of; 1) welfare, 2) installation of the Community Development Employment Projects (CDEP) scheme, 3) legislation enabling Traditional Land Owners and miners to negotiate agreements for training and employment of Indigenous people, and 4) programmes to encourage Indigenous entrepreneurship. This paper reports an Australian Indigenous entrepreneurial business (furniture making) initiated by the Gumatj clan of the Yolngu people in East Arnhem Land in the Northern Territory (NT) of Australia. These Indigenous people are employed in timber milling and transporting the milled timber to Gunyangara on the Gove Peninsula where it is dried and used to make furniture. Overcoming the literature documented barriers to Australian Indigenous entrepreneurship compelled the Gumatj to develop a business model with potential to foster pathways for other Indigenous small business endeavours.